2015
DOI: 10.1007/s00477-015-1032-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis for the downstream control section in the real-time flood control operation of a reservoir

Abstract: Many uncertainty factors are associated with the joint operation of a reservoir and its downstream river, which create risks in flood control decisions. Therefore, this paper proposes an analytical method for the estimation of the uncertainties and their risks in real-time flood control decisions. Three uncertainty factors, including reservoir discharge errors, forecasting errors of lateral inflows and river food routing errors are proposed and modeled as stochastic processes, and their internal transforming f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In previous studies, risk assessment has been conducted using fixed operation rules without optimization (Chen et al, 2015(Chen et al, , 2017Li et al, 2010;Yan et al, 2014). This study is distinct from all previous studies in that we explicitly incorporate flood forecast uncertainty into the optimization process.…”
Section: Risk Assessment For Flood Control Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, risk assessment has been conducted using fixed operation rules without optimization (Chen et al, 2015(Chen et al, , 2017Li et al, 2010;Yan et al, 2014). This study is distinct from all previous studies in that we explicitly incorporate flood forecast uncertainty into the optimization process.…”
Section: Risk Assessment For Flood Control Operationmentioning
confidence: 99%
“…However, gaps still exist between theory and application, and more efforts should be directed toward incorporating this type of forecast into water resources operations (Cloke & Pappenberger, 2009). Second, a number of risk analysis methods for flood control operation have been developed in recent years (Chen et al, 2015(Chen et al, , 2017Li et al, 2010;Tung et al, 2006;Yan et al, 2014). These methods can be used to calculate operation risks and evaluate the effect of flood forecast uncertainty on reservoir operation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most intractable difficulties is attributed to the uncertain and difficultly predictable inflow both in long-and short-term optimization (Chen et al 2015;Debnath et al 2015;Fan et al 2015). Zhao et al (2011) explored the effect of streamflow forecast uncertainty on real-time reservoir operation, and concluded that forecast uncertainty exerts significant effects.…”
Section: Introductionmentioning
confidence: 99%
“…We proposed a risk analysis method for reservoir real-time flood control operation by deriving the relationship between reservoir water levels and inflow forecast errors [24]. In addition, we also formulated an analytical method to calculate the risk of joint operation of a reservoir and its downstream river [25]. Generally, existing risk analysis methods can be divided into (1) direct integration method; (2) stochastic differential equation method; (3) Monte Carlo simulation; (4) structural reliability analysis method; and (5) fuzzy-sets based method.…”
Section: Introductionmentioning
confidence: 99%